(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
In view of the development of Brazilian studies in Social Skills (SS) in recent decades, it is important to analyze the scientific production in this area, since it allows the identify gaps and paths for future research. This study aimed to analyze the publications in the collection about SS articles named About Behavior and Cognition, using the methodology of bibliometric analysis. 27 chapters were selected and analyzed by the following criteria: year, institution, authors, type of study, and topics. Most authors were linked to universities, with nine works were from São Carlos Federal University. The authors who stood out were Del Prette and Falcone having five publications each. Regarding the classification of the chapters as to the type of study, 16 were classified as conceptual, five as correlational, four reports of experience, one case study, and one that could not be classified within these categories. Therefore these data characterize how the SS are portrayed in the collection, serving as the basis for the development of new research.